Strategies To Build Competitive Advantage Through Digital Marketing Communication - Axel Ramon Pattisina; Sumadi Sumadi (Cita konsultindo, 2023)
Technological developments have changed the business landscape in various sectors, including the hospitality industry. Hotel companies are now increasingly relying on digital marketing strategies to achieve a competitive advantage in an increasingly competitive market. Puri Asri Hotel Magelang is a company engaged in the provision of services and accommodation. This research aims to explore how the implementation of digital marketing by the marketing department of Puri Asri hotel can help generate competitive advantage, focusing on the communication aspect through digital marketing communication. The research conducted by the author uses a qualitative approach and observation method where the author conducts an internship at the company. By using SWOT analysis (Strength, Weakness, Opportunity, and Threat). The results showed that the use of digital marketing in the hospitality industry has provided a significant competitive advantage. Through digital platforms such as social media, websites, and email campaigns, hotel companies can increase their reach to potential guests, strengthen brand image, and increase interaction with customers. Appropriate and targeted communication through digital channels has also helped hotel companies to be more responsive to customer feedback, allowing for quick adjustments to changing market needs. Keywords: Marketing Strategy, Digital Marketing, Digital Marketing Communication, Competitive Advantage.